2014
DOI: 10.1128/jb.01698-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two UDP-Gal:GalNAc-Diphosphate-Lipid β1,3-Galactosyltransferases WbwC from Escherichia coli Serotypes O104 and O5

Abstract: c Escherichia coli displays O antigens on the outer membrane that play an important role in bacterial interactions with the environment. The O antigens of enterohemorrhagic E. coli O104 and O5 contain a Gal␤1-3GalNAc disaccharide at the reducing end of the repeating unit. Several other O antigens contain this disaccharide, which is identical to the mammalian O-glycan core 1 or the cancer-associated Thomsen-Friedenreich (TF) antigen. We identified the wbwC genes responsible for the synthesis of the disaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…a Neutral compounds were assayed by the AG1x8 method, and sugar-diphosphatelipids were assayed by the C 18 Sep-Pak method (23). Radioactive product was quantified by scintillation counting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…a Neutral compounds were assayed by the AG1x8 method, and sugar-diphosphatelipids were assayed by the C 18 Sep-Pak method (23). Radioactive product was quantified by scintillation counting.…”
Section: Resultsmentioning
confidence: 99%
“…After culturing at 6 h with either 100 g/ml ampicillin (GMD) or 50 g/ml kanamycin (RMD), IPTG (isopropyl-␤-D-thiogalactopyranoside) was added to make a 1 mM solution and proteins expressed overnight at room temperature. SDS-PAGE and Western blots (14,23) showed that the 4,6-dehydratase GMD and reductase RMD were well expressed. Isolated bacteria were sonicated in 90% phosphate-buffered saline (PBS)-10% glycerol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radioactive nucleotide sugars were from American Radiolabeled Chemicals. GalNAc and GlcNAc derivatives and inhibitors were synthesized as described previously (17)(18)(19)(20)(21). Glycopeptides and Gal␤1-3GalNAc␣-Bn derivatives were synthesized and kindly donated by Hans Paulsen, University Hamburg, Germany.…”
Section: Methodsmentioning
confidence: 99%